2015
DOI: 10.5489/cuaj.2603
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pubertal diagnosis of Klinefelter syndrome due to peno-scrotal malformations; Case report and review of literature

Abstract: We report a case of 4 months old infant diagnosed as Klinefelter syndrome associated with perineal hypospadias, severe ventral chordee and complete penoscrotal transposition. A review of previous reported cases was carried out. Penoscrotal malformations at birth are very rare in Klinefelter syndrome. Awareness of the current standard indications of Karyotyping can help early detection of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In 2015 the extensive retrospective reviews of the literature for boys with Klinefelter syndrome and associated penoscrotal malformations, revelead only 16 such cases [9]. The described malformations included hypospadiasis, penile chordee, bifid scrotum and penoscrotal transposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015 the extensive retrospective reviews of the literature for boys with Klinefelter syndrome and associated penoscrotal malformations, revelead only 16 such cases [9]. The described malformations included hypospadiasis, penile chordee, bifid scrotum and penoscrotal transposition.…”
Section: Discussionmentioning
confidence: 99%
“…Genital anomalies are generally not recognized as associated features [5,7,8]. Prepubertal diagnosis of Klinefelter syndrome, especially due to genital malformations, is a rare entity [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, those with genital abnormalities ranging from mild anomalies (isolated hypospadias, micropenis, cryptorchidism) to moderate undervirilization (penoscrotal abnormalities) have rarely been published in the literature. 1,[16][17][18] In these reports, though androgen insensitivity has been postulated as a possible mechanism, the AR gene was not analyzed in any of them. However, in three patients with both 47,XXY and genital abnormalities, Lee et al 1 demonstrated normal androgen-binding characteristics in genital skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Common characteristics of the syndrome are abnormal genitalia and gonads, with a progressive degeneration of testicular structure and function from childhood into adulthood. Although some infants may present with hypospadias (malformation of urethral opening, on underside of penis) (Cauldwell and Smith, ; Hodhod et al, ) or cryptorchidism (undescended testes) (Schwartz and Root, ), the gonads and genitalia of KS infants generally fall within normal expectations (Ratcliffe, ). Prepubertal KS males may have a penis that is normal (Salbenblatt et al, ) or reduced (Cauldwell and Smith 1972; Ross et al, ; Zeger et al, ) in size.…”
Section: Reproductive and Endocrine Abnormalitiesmentioning
confidence: 99%